Modification of compressive strength of cement mortar by oil palm shell ash - Lim, Yen Ping (2014)
Oil palm shell (UPS) ash is one of the waste products from industry sector during the palm oil extraction process: Since the ash is being light and in small size of particle, it is easily to carry away by wind. As a result, the smog causes the air pollution which reduces the visibility and eventually creates traffic hazard. In order to reduce the waste products extracted from the UPS which is being dumped without a proper management, it will cause in the result of atmospheric pollution, if possible, among other applications, to use it as the admixture in the cement mortar. Therefore, in this research, the main characteristics of the cement mortar are presented and compared with those of the additional of admixtures. The experimental study shows the possibility and effect of adding in the UPS into the cement mortar, for the improving on its compressive strength. This research, was conducted to determine the compressive strength of cement mortar by using different percentage of OPS ash. Besides, the research also examines the modulus of elasticity behavior on cement mortar with the present of admixture. The size of cube specimens used was 1 00m x 100mm x 100mm. About five types of sample which containing 0%, 1%, 2%, 3% and 4% of UPS ash were tested. Meanwhile 0% of UPS ash was used as the control sample. Compressive strength of the cement mortar made with and without UPS ash was determined at 7 and 28 days. The findings revealed that the 4% proportion of UPS ash added in the cement mortar is suitable. The Compressive' strength for mix type of 46% cement + 50% sand + 4% UPS ash reached a maximum value which is 46.378 MPa and much greater than mix type of 50% cement + 50% sand (control sample) which possesses 42.839 MPa. The UPS ash up to 4% does not have negative effect on cement mortar quality. The time to failure increases with the increases of force applied. It showed a positive result on the modulus of elasticity towards cement mortar.